Treatment Trajectories During and After a Medication Trial for Opioid Use Disorder: Moving from Research as Usual to Treatment as Usual. Issue 4 (July 2020) - Fishman, Marc; Vo, Hoa T.; Burgower, Rachael; Ruggiero, Michael; Rotrosen, John; Lee, Josh; Nunes, Edward
Abstract : Objectives: The effectiveness of treatment incorporating relapse prevention medications for opioid use disorder (OUD) is typically examined in research using rigidly predefined endpoints of success versus failure, usually over a single episode of care. But this perspective may not adequately portray the nonlinear trajectories typical of real-world treatment courses in this chronic, remitting, and relapsing disorder. Methods: This descriptive study examined 12-month treatment trajectories of n = 60 patients enrolled at a single site of a larger multisite randomized controlled trial examining the comparative effectiveness of buprenorphine versus extended-release naltrexone. While the parent study provided medication treatment through the research protocol for 6 months, this study documents treatment up to 12 months, including medications, provided through standard community resources (treatment as usual) outside of the protocol. Results: Some patients continued medications past the end of the study intervention, whereas others did not. Some patients initiated medications other than the one assigned by the study. Some patients switched from 1 medication to the other. Many patients returned to treatment after 1 or more periods of dropout and/or relapse. Patients utilized multiple episodes of bed-based care, including short-term acute residential and long-term residential treatment, and also recovery housing supports. Described trajectories are also depicted graphically. At 12 months, while rates of continuous treatment retention were low (8%), rates of cross-sectional treatment engagement including return to treatment after drop out were higher (35%). Conclusions: This description of nonlinear treatment trajectories highlights the potential benefits of flexibility and optimism in the promotion of re-engagement, despite interim outcomes that might traditionally be considered "failure" endpoints.